Iron nanoparticle/carbon nanotube composite as oxidase-like nanozyme for visual analysis of total antioxidant capacity - Junlin Liu; Sophia Xie; Nan Wang; Zhongyue Sun; Lina Tang; Guo-jun Zhang; John Tressel; Yulin Zhang; Yujie Sun; Shaowei Chen (Food Chemistry: X)
Total antioxidant capacity (TAC) is an important indicator for assessing the merit of natural plants and foods. Herein, a visual TAC assay is developed based on the oxidase-like activity of nitrogen-doped carbon nanotubes loaded with Fe nanoparticles (FeNPs@NCNT), which is prepared via high-temperature pyrolysis of metal-organic framework precursors and can catalyze the oxidation of colorless o-phenylenediamine (OPD) to colored 2,3-diaminophenazine (DAP). The addition of antioxidants (e.g., quercetin) impedes the formation of DAP, diminishing the color change, which can be analyzed via the RGB values obtained with a smartphone color-recognition APP, “Color Picker”. The change of the optical signal can also be analyzed in the fluorescence mode. These two detection modes yield consistent TAC analysis of actual plant samples, in accord with results from the standard ABTS method. Results from this study highlight the unique potential of nanozymes in the development of effective TAC analysis platforms for natural plants and food.